(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The study examines the challenges associated with the application of circular economy principles for construction and demolition waste management in South East Nigeria. A survey research design was adopted, utilizing structured questionnaires to collect data from building construction professionals involved in ongoing projects across Anambra, Enugu, Abia, Ebonyi, and Imo States. The target population consisted of 1,653 key stakeholders, including 333 clients, 894 contractors, and 426 consultants engaged in public projects. A purposive sampling technique was employed to select a sample size of 322 participants, comprising 131 contractors, 40 clients, and 151 consultants proportionally distributed across the five states. The study's findings, assessed using a mean decision rule of 2.50, reveal significant barriers to the effective adoption of circular economy principles in the study area. Key challenges include the limited availability of infrastructure and technology necessary for sorting, recycling, and reuse of construction and demolition waste, which impedes resource recovery within a circular economy framework. A lack of collaboration and coordination among stakeholders disrupts the seamless flow of materials and information essential for implementing circular economy initiatives. Furthermore, the insufficient integration of circular economy principles into current waste management practices highlights a gap between theoretical frameworks and practical applications. Resistance to change within the construction industry, stemming from entrenched practices and concerns about cost or feasibility, further exacerbates the issue. To advance the adoption of circular economy practices, the study recommends the provision of adequate infrastructure and technology to facilitate efficient waste sorting, recycling, and reuse. Addressing these barriers is critical for optimizing resource efficiency, minimizing environmental impact, and promoting sustainability in construction waste management.